Intensity of Use Hypothesis: Analysis of Selected Asian Countries with Structural Differences - Soile, Ismail Oladimeji (International Journal of Energy Economics and Policy, 2012)
Several efforts have been made to estimate the relationship between intensity of metal use and per capita income at different levels with results supporting the hypothesis that metal consumption per unit of GDP initially increases, peak and later decline with rising income per head. This paper estimates the intensity of copper use curves for three Asian countries with different economic structure to show that the I-U hypothesis significantly underplay the influence of economic structure and other technological innovations by its exclusive emphasis on per capital income. The results are in general conformity with the notion that the intensity of material use (I-U) is higher for industrial and very low for service based economies. Though the finding is mixed in the agrarian country considered, the paper suggests the need for further research to corroborate this outcome. Keywords: Asian countries; economic development; technological change; mineral resources; material use; metals. JEL Classifications: O1; O3; Q3